Thematic Content Analysis of Theological, Moral, and Spiritual Messages in the 7th Ngaji Tasawuf Session (2025) at Nurul Jadid Islamic Boarding School - Suwito, Suwito; Wazis, Kun (JURNAL AT-TURAS, 2025)
The proliferation of digital preaching raises concerns about the marginalization of contemplative religious traditions. This study addresses the research gap in analyses of how classical sufistic preaching is rearticulated for and through digital media. The study examines the da’wah delivered by KH. Moh. Zuhri Zaini during the 7th Ngaji Tasawuf session (2025) at Nurul Jadid Islamic Boarding School, a program also broadcast live on the pesantren’s YouTube channel. The purpose is to identify and classify the dominant theological, moral, and spiritual themes and to interpret their communicative functions in a mediated setting. Using qualitative content analysis, the study applies inductive coding and thematic categorization to the full transcript, triangulated with video recordings and relevant literature. Results show four interrelated thematic clusters; theological (tauhid and existential awareness), moral (niyyah, sincerity, and ethical prioritization), spiritual (dhikr, tafakkur, tazkiyah), and social (digital conduct and communal responsibility) which together constitute a coherent model of Sufistic preaching adapted to online formats. The paper proposes a preliminary framework of “digital Sufistic communication” that conceptualizes how pesantren ritual discourse is remediated for participatory digital publics. Implications include suggestions for (a) designing digital preaching frameworks that preserve contemplative depth, (b) pesantren pedagogy responsive to mediated audiences, and (c) future empirical testing of the proposed framework across other pesantren livestreams.